Transgressive pedagogies in a climate-constrained Africa: grounding climate change education and sustainability learning in local communities - Manteaw, Bob Offei; Boafo, Yaw Agyeman; Owusu, Erasmus Henaku; Enu, Kirk B.; Amoah, Antwi Boasiako (Frontiers in Education, 2025)
IntroductionDespite global recognition of the climate crisis, higher education often remains rooted in traditional, theory-focused paradigms emphasizing economic growth, thereby hindering necessary structural transformations. This study argues for an urgent shift towards practical and experiential learning in higher education, particularly in sustainability learning and climate change education, by adopting transgressive pedagogies and place-based approaches grounded in local communities.MethodsThis study employed a series of field learning journeys within Ghana to investigate the impact of practical engagements on students’ understanding and appreciation of environmental, social, and climate change challenges. Data was collected to assess changes in students’ attitudes toward climate change and sustainability learning, their orientation for environmental stewardship, social change advocacy, and climate action, as well as their dispositions and competencies for partnerships and collaborations in addressing socioecological challenges.ResultsThe findings demonstrate marked positive changes in students’ attitudes toward climate change and sustainability learning. Furthermore, there is evidence of enhanced orientation for environmental stewardship, social change advocacy, and climate action among the students. The study also reveals improvements in students’ dispositions and competencies to utilize partnerships and collaborations for addressing socioecological challenges.DiscussionThis study highlights the critical importance of place in sustainability and climate change education. Grounding teaching and learning in local contexts through practical, experiential approaches fosters the development of locally relevant competencies and facilitates essential connections between theoretical knowledge and lived experience. The findings underscore the potential of place-based and transgressive pedagogies to cultivate environmental stewardship, social change agency, and collaborative problem-solving skills in higher education.